Assessment of Genetic Diversity of Cedrus deodara Roxb. through Random Amplified Polymorphic DNA - Rai, Kirti Chamling; Chauhan, Priti; Rawat, Anita; Saha, Romeet; Ginwal, H. S. (Indian Forester, 2020)
Indian cedar (Cedrus deodara) is an important conifer of the western Himalayas. It has high ecological as well as economical value and due to its high demand for timber, the natural population of this species is gradually declining under the pressure of over exploitation. RAPD markers were used to study genetic variation in three natural populations of C. deodara using 10 primers. The study indicated that C. deodara populations maintained moderate level of genetic diversity (mean Ht = 0.233) with more variation among the populations as compared to within population diversity (mean Hs = 0.162). The among population differentiation was relatively low (mean Gst = 0.210) due to the high level of gene flow (mean Nm = 4.486) between the populations under study. A dendrogram constructed for the three populations of C. deodara using the UPGMA method clustered Punan in Shimla and Churah Forest Division in Chamba district of Himachal Pradesh together with the similarity co-efficient of 0.933 whereas, the population from Lohaghat in Uttarakhand was segregated separately. The study also revealed that the population from Punan, Himachal Pradesh was the most genetically diverse population which exhibited the highest percentage of polymorphic loci.